Advances in limnological research in Earth's drylands - Barbosa, Luciana Gomes; Amorim, Cihelio A.; Parra, Gema; Laço Portinho, Jorge [UNESP]; Morais, Manuela; Morales, Eduardo A.; Menezes, Rosemberg Fernandes (Taylor & Francis, 2020)
Drought is an important driver of change in aquatic ecosystems and generally acts as a filter to select biological traits capable of persisting under severe environmental circumstances. Drylands are highly vulnerable to climate change and increases in climate variability. Consequently, an increase in the processes of eutrophication, salinization, and habitat desiccation may be observed in response to the loss of the hydrological connectivity. The International Network on Limnology of Drylands (INLD) was created with the overall goal of understanding the functioning and conservation status of aquatic ecosystems in drylands globally. INLD was made official in 2016 through the International Society of Limnology. Its objectives are to (1) assess the current state of biological diversity in dryland aquatic ecosystems, (2) evaluate the multiple environmental stressors acting in drylands, and (3) develop models to predict effects of global change on drylands. This special issue, Limnology of Drylands, consists of 10 manuscripts focused on the effects of environmental pressures, including global warming, on the biodiversity and distribution of aquatic communities in drylands.
Keywords: arid; biodiversity; climate change; dry-subhumid; hyper-arid; multiple stressors